Early childhood care and education development in Malaysia: Early recognition and way forward / Nor Shamimi Muhamad Ridza, Yarina Ahmad and Thenmolli Vadeveloo - Muhamad Ridza, Nor Shamimi; Ahmad, Yarina; Vadeveloo, Thenmolli (2021)
Early childhood care and education (ECCE), according to UNESCO covers the period from birth to eight years of age old (UNESCO, 2021). During this period, the brain development of children is at its peak and is highly influenced by their surrounding environment. According to the Sustainable Development Goals blueprint by the United Nations, section 4.2 of the fourth goal aims by 2030 that all girls and boys have access to quality early childhood development, care, and pre-primary education so that they are ready for primary education. The ECCE system in Malaysia is categorized into two age groups, which are 0-4 years old and 4-6 years old (Chiam, 2008). The first group is referring to early childhood care programs that are monitored by the Department of Social Welfare under the supervision of the Ministry of Women, Family, and Community Development. On the other hand, the second group that is referring to early childhood education programs is monitored by several agencies or ministries such as the Ministry of Education (MoE), the Department of National Unity and Integration under the Prime Minister Department, and Ministry of Rural and Regional Development. This paper aims to discuss the ECCE development in Malaysia through evaluating The Five-Year Malaysia Plans. Subsequently, this paper argues for five phases of ECCE evolution and development in Malaysia from the 1980s until recently.